Fire safety management in heritage buildings: the current scenario in Malaysia - Salleh, Nurul Hamiruddin; Ahmad, A Ghafar (2009)
In Malaysia, there are many heritage buildings with an architectural and historical significance that influenced by several architecture styles including a traditional Malay architecture, the Portuguese architecture, the Dutch architecture, and the architecture styles brought by British (e.g. Moorish, Tudor, Neo-Classical and Neo-Gothic). Most of them are worthy to be listed as Heritage Buildings or National Heritage Buildings under the National Heritage Act 2005 (Act 645). The Malaysian government is undertaking many efforts to promote conservation and preservation of heritage buildings in the country. Some of the buildings have been changed to different functions from its original (adaptive-reuse) such as into museums, libraries, offices or hotels. It is however, in the past few years there are few priceless heritage buildings were badly damaged or burnt down by fire includes the People Museum, Melaka (2001), Rumah Pak Ali , Gombak (2003) and Sarawak Club, Kuching (2006). In one case, it was given a total loss approximately up to MYR 5 millions. Fire is one of the greatest threats to heritage buildings not only to the building’s occupants but also to the building’s fabric and contents. Heritage buildings are irreplaceable but vulnerable to fire as there is a combination of several factors: large scale buildings; flammable priceless contents; large numbers of visitors; and existing structures weak on fire resistance. Unfortunately, until today, there are relatively no sufficient legislations or guidelines on fire safety for heritage buildings in Malaysia. In fact, the Fire and Rescue Department of Malaysia (FRDM) stressed the safety of life is the ultimate principle of fire safety in a building. Property protection which includes protection to building’s fabrics and contents of heritage buildings is not really been prioritised. The purpose of this research is to investigate the current fire safety management in heritage buildings in Malaysia through a series of interview and observation surveys. In this research, thirty seven heritage buildings have been surveyed as a building sampling. The finding found that most of the buildings are still having a poor fire safety management. From the survey, seventeen leading fire safety management problems in the buildings have been identified.